PENGUASAAN METODE DIAGRAM PANAH SEBAGAI LANGKAH AWAL PEMAHAMAN TERHADAP DASAR-DASAR PENYUSUNAN NETWORK PLANNING METODA JALUR KRITIS - Sumardjito Sumardjito (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2011)
In order to learn network planning, need an understanding of some of theprovisions. A project is the overall effort in the form of networks planning. The projectconsists of a series of events and activity that construct a system and cycles thatboils down to an outcome. To create an operational plan, project hardwareincluded/required a tool that will give an idea clearly relationship, such as device isnetwork planning. On the operational level, the project network planning method isthe Critical Path Method (CPM). To understand the readings and analysis CPM isnecessary basics Arrow Diagramming Method. In this method will be elaborated andrelationship between activities with other activities, one event relationship with otherevent system and thus forming the structure of work processes. In other words, inthe planning of the CPM, in the first of finishing is elaborated arrow diagram. Thatsmean the network planning has finish a half procces, so the next step will be easilyto finish all diagram. Network planning CPM that initially looks like very complicatedand abstract, but with an understanding of the arrow diagram will be known quickly,which where activities having relationship that are free and which ones areinterdependent, and which part is the critical.Keywords : Network planning, Critical path method